EFFECTIVENESS OF ANDROID-BASED LEARNING MEDIA WITH GUIDED INQUIRY LEARNING MODELS ON SCIENCE PROCESS SKILLS - Herman Jufri Andi; Lubna Dwi Masluhah; Suprianto Suprianto; Chairatul Umamah (JURNAL EDUSCIENCE, 2023)
Utilization of science and technology in the field of education further enhances and expands knowledge, so that in conveying a lesson in the classroom, the teacher becomes more creative and innovative. The latest technology in education for the development of learning media is Android. The use of Android in the form of a smartphone is one of the media that is often used by the general public, especially students. Researchers want to know the effectiveness of the use of Android-based media with the guided inquiry learning model on students' science process skills. This research is a quasi-experimental study with a pretest-posttest control group design. The population of this study was class X, even semester, of MA Al-Djufri Blumbungan, Pamekasan. In this study, there were two sample groups consisting of one control class and one experimental class. To find out the effectiveness of effect size calculations using the SPSS version 24 program and Microsoft Excel, these calculations yielded a value of 0.723, which is in the high category with an interpretation of the Cohen's value of 79%. This is obtained because, with the use of Android-based media and the guided inquiry learning model, students are more enthusiastic and active in the process of teaching and learning activities, which makes it easier for them to carry out the experiments given and to prepare reports better.Keywords: Android based media, guided inquiry, science process skillsAbstrak Pemanfaatan ilmu pengetahuan dan teknologi bidang pendidikan lebih meningkatkan serta memperluas pengetahuan agar dalam menyampaikan suatu pembelajaran didalam kelas guru menjadi lebih kreatif dan inovatif. Teknologi terkini dalam pendidikan untuk pengembangan media pembelajaran adalah android. Penggunan android berupa smartphone merupakan salah satu media yang sering digunakan oleh masyarakat umum, khususnya pelajar. Peneliti ingin mengetahui efektifitas dari penggunaan media berbasis android dengan model pembelajaran inkuiri terbimbing terhadap keterampilan proses sains siswa. Penelitian ini merupakan penelitian Quasy-Eksperimental dengan desain pretes-posttest control group design. Populasi penelitian ini adalah kelas X semester genap MA Al-Djufri Blumbungan, Pamekasan. Sedangkan sampel dari penelitian ini ada dua kelompok sampel yang terdiri dari satu kelas kontrol dan satu kelas eksperimen. Untuk mengetahui keefektifan dilakukan perhitungan effect size menggunakan program SPSS versi 24 dan Microsoft excel, dari perhitungan tersebut diperoleh 0,723 yang masuk kategori tinggi dengan interpretasi nilai Cohen’s 79%. Hal ini didapatkakan karena pada penggunaan media berbasis android dengan model pembelajaran inkuiri terbimbing siswa lebih antusias dan lebih aktif dalam proses kegiatan belajar mengajar serta mempermudah siswa dalam melakukan percobaan yang diberikan dan mampu menyiapkan hasil laporan dengan lebih baik.Kata Kunci : Media berbasis android, inkuiri terbimbing, keterampilan proses sains siswa.